2021
DOI: 10.1177/09603271211054436
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the anti-inflammatory effects of caffeic acid phenethyl ester in a model of λ-Carrageenan–induced paw edema in rats

Abstract: In the present study, it is aimed to evaluate the effects of caffeic acid phenethyl ester (CAPE) against acute paw inflammation induced by carragenan (Carr) at macro and micro levels. Therefore, in this study, 1 hour after administering intraperitoneal of indomethacin (Ind) or CAPE (10 and 30 mg/kg body weight) to Sprague Dawley rats, Carr was injected intraplantarly into their right paws. The paw volumes of the rats were measured with a plethysmometer until the 4th hour. Also, X-ray and thermal camera images … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…Antioxidant enzymes and compounds play a key role in maintaining the oxidant/antioxidant balance in the organism 41 . Cells are exposed to oxidative stress as a result of decreased antioxidant activity and depletion of antioxidant compounds, and this increases oxidants 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant enzymes and compounds play a key role in maintaining the oxidant/antioxidant balance in the organism 41 . Cells are exposed to oxidative stress as a result of decreased antioxidant activity and depletion of antioxidant compounds, and this increases oxidants 42 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the effects of QUE on CYP-induced lung toxicity were investigated by evaluating oxidative stress, inflammation, Antioxidant enzymes and compounds play a key role in maintaining the oxidant/antioxidant balance in the organism. 41 Cells are exposed to oxidative stress as a result of decreased antioxidant activity and depletion of antioxidant compounds, and this increases oxidants. 42 Pesticides such as CYP cause excessive ROS formation, leading to a decrease in plasma or tissue antioxidant values.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of natural extract might be explained by its chemical compounds that we identified through HPLC determination: flavonoids (naringenin, kaempferol, rutoside and their derivatives) that have been previously presented in the literature as part of this natural compound [ 32 , 33 , 34 ]; phenolic acids (caffeic and chlorogenic acids) mentioned by Bayram and Ozturkcan [ 35 ]; but also chrysin, hyperoside and luteolin. Several studies presented caffeic acid as an antioxidant [ 36 ], anti-inflammatory [ 37 ] and even a smooth muscle relaxing compound, as Siva et al showed in their study performed in organ bath using the rat thoracic aorta [ 38 ]. The other phenolic acid identified in Cornus mas L. extract, chlorogenic acid, was found in our previous studies as an efficient antioxidant and anti-inflammatory element, in a dose-dependent manner [ 39 , 40 ], Wu et al described this natural compound as anti-atherosclerotic [ 41 ], Hada et al as a potent inhibitor of aorta senescence in their study performed on mice with saline or angiotensin II administration [ 42 ], and many other studies indicated the beneficial effects of this acid.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress causes NF‐κB activation which leads to increased expression of pro‐inflammatory cytokines, thus triggering the inflammatory process 30,39–41 . The interaction between ER stress and inflammation has been extensively studied in cell types with metabolic or immune functions, and inflammation has been associated with unfolded protein response (UPR) activation to promote disease development 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress causes NF-κB activation which leads to increased expression of pro-inflammatory cytokines, thus triggering the inflammatory process. 30,[39][40][41] The interaction between ER stress and inflammation has been extensively studied in cell types with metabolic or immune functions, and inflammation has been associated with unfolded protein response (UPR) activation to promote disease development. 38 In many previous studies, it has been reported that organophosphate compounds, including MLT, trigger inflammation by increasing the expression of pro-inflammatory cytokines in various tissues.…”
Section: Discussionmentioning
confidence: 99%